Alessandro Fabbri papers - Fabbri, Alessandro, 1877-1922.
Correspondence, biographical material, memorabilia, and photographs. Correspondence relates to Fabbri's service as officer in charge of the radio station at Otter Cliffs, Bar Harbor, Me., during World War I, and hence contributes to the early history of transatlantic radio communication. One item is described as the original wireless message from the German Government received at Otter Cliffs, November 10, 1918 (the day before the Armistice), asking for mitigation of conditions imposed by the Allies. Includes correspondence of Samuel C. Hooper.
Naval reserve officer.
Collection material in English, with German.
Keywords: Hooper, Samuel C. -- Correspondence; United States. -- Navy -- Radiomen; Radio, Military -- Germany; Radio, Military -- United States; Radio stations -- Maine -- Bar Harbor; World War, 1914-1918 -- Communications; World War, 1914-1918 -- Peace; Otter Cliffs Radio Station Site (Me.); Naval officers